2021
DOI: 10.7196/sajch.2021.v15i1.01756
|View full text |Cite
|
Sign up to set email alerts
|

Exploring determinants of under-5 stunting in Malawi using a generalised linear mixed model

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.Stunting is a risk factor for poor health and psychosocial development arising from in utero and/or early childhood malnutrition. [1] As the most prevalent form of child malnutrition, stunting remains a public health problem. [2] Although efforts have been put in place by various stakeholders to ameliorate these negative impacts through several nutrition interventions, [1,3,4] reduction in the trend of malnutrition in under-5-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Supporting this assertion, a Brazilian study found positive correlations between haemoglobin (Hb) levels and HAZ, even after controlling for age [ 30 ], which ultimately led to CAS. Furthermore, Afolabi and Palamuleni reported that the likelihood of stunting was higher among anaemic children [ 31 ]. Likewise, the study identified children born of anaemic mothers and mothers with short/very short stature as being significantly associated with higher odds of childhood CAS.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this assertion, a Brazilian study found positive correlations between haemoglobin (Hb) levels and HAZ, even after controlling for age [ 30 ], which ultimately led to CAS. Furthermore, Afolabi and Palamuleni reported that the likelihood of stunting was higher among anaemic children [ 31 ]. Likewise, the study identified children born of anaemic mothers and mothers with short/very short stature as being significantly associated with higher odds of childhood CAS.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent research from Rwanda, Gambia, Ethiopia, India, Uganda [12][13][14][15][16] , and Indonesia 17,18 indicates that the causes of child stunting vary and are multifactorial. Stunting determinants include low birth weight [18][19][20][21][22][23] , food insecurity 19,[23][24][25][26][27] , birth spacing 7,[28][29][30] , child age [31][32][33][34] number of children [35][36][37][38] , and the inability to breastfeed exclusively [39][40][41][42] . Stunting increased significantly in children living in households with three or more children under five years of age, households with 5-7 household members, children whose mothers attended less than four antenatal care services during pregnancy, males, 12-23 months old, and low birth weight 43 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to nutritional and other environmental factors, genetic causes of anaemia are common in children of Malawi (Linnemayr & Alderman, 2008). The study investigating the determinants of stunting among under five years children in Malawi by (Afolabi & Palamuleni, 2021) showed that Children who were female from wealthier households whose mothers were overweight/obese aged 25 -34 years had at least a secondary level education were less likely to be stunted. Anaemia in Angola, Malawi and Senegal was found to be associated with the mothers' level of education, household wealth status and child's age, whereas, malnutrition was found to be associated with type of residence, household wealth status, mother's level of education and child's age .…”
Section: Introductionmentioning
confidence: 99%